Like that Lah: Malaysian undergraduates’ attitudes towards localised English - Tan, Debbita Ai Lin; Lee, Bee Choo; Shaidatul Akma Adi Kasuma,; Malini Ganapathy, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Native-like English use is often considered the standard to be achieved, in contrast to nonnative English use. Nonetheless, localised English varieties abound in many societies and the growth or decline of any language variety commonly depends on how it is perceived; for instance, as a mere tool for functionality or as a prized cultural badge, and only its users can offer us insights into this. The thrust of the present study falls in line with the concept of language vitality, which is basically concerned with the sustainability of non-global languages. This paper first explores the subject of localisation and English varieties, and then examines the attitudes of Malaysian undergraduates towards their English pronunciation and accent, as well as their perceptions of Malaysian English. A 26-item questionnaire created by the researchers was utilised to collect data. It was also tested for reliability, with returned values indicating good internal consistency for all constructs, making the instrument a reliable option for use in future studies. A total of 253 undergraduates from a public university responded to the questionnaire and results revealed that overall, the participants valued their local-accented English and the functionality of Malaysian English, but regarded this form of the language as substandard. They also considered it important for Malaysians to achieve native-like English use, particularly for the attainment of better educational and economic prospects. These findings provide direction for educational policy-planning as well as English language teaching, and are of relevance to research on English varieties, including the preservation of linguistic heritage.